Security cooperation in South Asia: Overview, reasons, prospects - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2014)
For many years now, South Asia has been regarded as a region of chronic instability and economic disintegration. But aside from the different conflicts, various forms of security cooperation have also developed between India and its neighbors. The main reasons for this development are due to changes in India's South Asia policy and rapprochement with regard to national threat perceptions. Today, in most states the main security challenges are seen as coming from domestic rather than external threats. This has created new opportunities for security collaborations, which were previously unthinkable. India and its neighbors increasingly share the belief that security can only be achieved through cooperation and no longer through confrontation. The different forms of security collaboration can be seen as the starting point for a regional security architecture. However, because of the political constellations, it will remain an informal architecture that offers hardly entry points for a closer institutionalization. (SWP Research Paper)
Keywords: 320